Service Quality, Patient Satisfaction, and Patient Loyalty at Pavilion RSGM Unpad: A Quantitative Analysis - Salsabila Riaz Nisar; Hendrati Dwi Mulyaningsih; Rini Lestari (Journal of Healthcare and Biomedical Science, 2026)
This study aims to analyze the role of service quality and patient satisfaction in shaping patient loyalty at the Pavilion of RSGM Unpad. Patient loyalty matters not only for institutional competitiveness but also for continuity of care, service utilization, and the long-term sustainability of specialized health services, yet evidence from premium dental hospital units in Indonesia remains limited. The research employed a quantitative cross-sectional explanatory survey design. The study sample consisted of 188 patients, selected through convenience sampling, and data were collected using a structured questionnaire measuring perceptions of service quality, satisfaction, and loyalty. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects among the variables. The results show that service quality significantly influences patient loyalty, and patient satisfaction also has a significant effect on loyalty; together the two predictors explain 72.5% of the variance in loyalty. The findings highlight that dominant factors such as the professionalism of medical staff, timeliness of service, and comfort of supporting facilities play a central role in shaping loyalty. The study contributes empirical evidence on the service quality–satisfaction–loyalty pathway in a specialized Indonesian dental hospital setting and offers practical implications for quality improvement, patient-centered care, and the retention of patients in such services.